Therapeutic management of appendicular osteoarthritis in dogs using platelet rich plasma (PRP) and pentosan polysulphate sodium - Suryavanshi, Nitesh; Singh, Randhir; Jawre, Shobha; Verma, Yamini; Barhaiya, Rakesh Kumar; Mishra, Apoorva; Das, Babita; Shahi, Apra (Indian Journal of Veterinary Surgery, 2026)
The present study was conducted on 12 dogs suffering from appendicular joint osteoarthritis (OA) presented at Veterinary Clinical Complex, Jabalpur during the study period of six months. The dogs were equally distributed into three treatment groups. In group I, the dogs were treated with inj. carprofen 4 mg/kg body wt, s.c. for 5 days and tab. glucosamine hydrochloride 500 mg, chondroitin sulphate 400 mg, manganese sulphate 5 mg, Boswellia serrata 50 mg, Withania somnifera 50 mg, Vitamin C 12.5 mg orally for 30 days. The dogs of group II were treated as in group I with addition of an intra-articular injection of 1 mL platelet-rich plasma (PRP) on days 0, 7, 14, 28 and 45. The dogs of group III were treated as in group I with addition of an intraarticular injection of 1 mL PRP and pentosan polysulfate sodium 3 mg/kg body wt, s.c. on days 0, 7, 14, 28 and 45. The results indicated that both the treatment regimens (group II and III) were equally effective in reducing osteoarthritic pain; however, significant (P